The body and work (Body and society. Sociology of the body in research and theoretical concepts, 2023)
This chapter tackles the issue of relations between the bodies of individuals and the social situation of work. Posts, employment conditions, workplaces and professional identities are gaining significance in contemporary societies, in relation to the transformations of the last decades in particular. Thus, it is worth paying attention to the fact that employees are embodied social actors. Their health and safety depend on the activities in the workplace in terms of individual, macrosocial, or even global dimensions. In the first part of the chapter, the presented issues relate to the human body in a social situation of work. The relation between the body and the work in sociology is discussed, including the studies of the industrial era, which were conducted by, i.a., Karl Marx or Max Weber, and the achievements of the studies on workplace relations. The way in which the issue of the body in the context of work was taken up by the classic sociological authors is also presented. The further parts of this chapter explore some of the more specific notions and key concepts concerning the relations of the body and the work in sociological theories and research. The chapter also tackles the issues related to sex work, reproductive work, emotional work, or the constructivist nature of OHS regulations. The issue of work in the professions dealing with the body work is also raised, e.g. hairdressers, fitness instructors, dentists, care assistants, doctors, nurses, cleaners or therapists.